Marketing Strategies in Increasing The Income of Traders in Sumedang City Market - Karmila, Ila; Rizqiya, Shinta (SINTESA, 2024)
This research is about marketing strategies in increasing the income of market traders in Sumedang City Market. The problem faced by traders in the Sumedang City Market is the problem of decreasing the income of market traders, this is due to a lot of competition which is quite tight because of the establishment of many modern markets that offer a variety of products in the government such as Toserba Griya Sumedang and Plaza Asia Sumedang, besides that the traders make various innovations so that the Sumedang City market does not lose out on competition with other traditional markets. The method used is qualitative research method. The data collection techniques used were interviews, documentation studies, and observation. The results of the study prove that to increase the income of traders in the Sumedang City Market, namely by building and renovating the Sumedang City Market Sumedang neatly and cleanly, besides that implementing various appropriate marketing strategies will help traders to increase the income and welfare of Sumedang City Market traders